The Role of Augmented Reality(AR)in Construction Project Planning and Execution (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
One of the most exciting advancements in modern construction is the use of augmented reality (AR). AR technology can revolutionize how construction teams work, from design visualization and collaboration to on-site construction assistance and improved long-term maintenance. Augmented reality provides various benefits that can help companies create the world of tomorrow more efficiently and effectively. It enhances efficiency and accuracy by overlaying digital information, like 3D models and blueprints, onto the physical job site. Its roles include improving visualization for better planning, ensuring construction matches design through on-site checks, boosting safety via simulated training, facilitating remote assistance and collaboration, and streamlining maintenance and inspections by providing real-time data access.It provides a range of benefits that can help companies create the world of tomorrow more effectively and efficiently. Let’s explore some of the benefits of AR in construction.Now, augmented reality can incorporate CAD and BIM data to create detailed 3D models that overlay the real world. CAD has enhanced accuracy and consistency. BIM has created more detail and collaboration.AR is the next natural step for construction innovation, and it can enhance design, construction, maintenance, and on-site management.Augmented reality can share information and data in real-time, allowing professionals from different disciplines to work together more effectively. Miscommunication and project management errors can result in higher costs and missed deadlines, which may lead stakeholders to lose confidence.AR allows workers to visualize and discuss design plans, share measurements, and track progress. More detailed data enables site managers, contractors, and superintendents to keep detailed reports and adjust work accordingly
Keywords: 3D models; BIM data; augmented reality (AR)